Formulasi dan Uji Inhibitor Tirosinase Masker Peel-Off Ekstrak Etanol 96% Kulit Buah Jeruk Nipis (Citrus aurantifolia) - Ari Widayanti; Rini Prastiwi; Kartika Tiara Wijayanti (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Tyrosinase is an enzyme that is widely distributed in microorganisms, plants and animals. Tyrosinaseis the main enzyme involved in the biosynthesis of melanin. Melanin has a very important role in skin protection, especially against exposure to ultraviolet rays which are harmful to the skin. This study aims to test the tyrosinase inhibitor in the peel-off mask of lime peel extract (Citrus aurantifolia). Lime peel extract is formulated into a peel-off mask with extract content of 0% (F1), 15% (F2) and 25% (F3) respectively and with the gelling agent PVA (Polyvinyl alcohol). The physical stability test was carried out by measuring the pH, the results obtained were F2 pH 6.85 and F3 pH 6.78. The analysis of tyrosinase inhibitor activity was carried out using a UV-Vis spectrophotometer and seen from the percent inhibition value obtained. The percent inhibition results obtained from the peel-off mask of lime extract were 17.89% (F2) and 18.86% (F3). Lime peel has the potential as a tyrosinase inhibitor.